Economic evaluation guidelines in Latin America: a current snapshot. (October 2010) - Augustovski, Federico; Garay, Osvaldo Ulises; Pichon-Riviere, Andres; Rubinstein, Adolfo; Caporale, Joaquín E
Economic evaluation guidelines are widespread in developed countries with fourth hurdle systems but as of yet not in Latin America. In the present article, a systematic search was conducted in order to retrieve regional guidelines in PubMed, Latin American and Caribbean Health Sciences Literature (LILACS) and the gray literature. Four national guidelines were found: Brazil, Colombia, Cuba and Mexico. We report a thorough review of these documents, as well as a comparison among them. We conclude that, despite some differences found, they are broadly similar, and are broadly in accordance with international documents. The existence of these documents, together with other experiences in the region that explicitly use economic evaluation information for health decision making clearly shows that this global tendency is gaining momentum in Latin America, although there is still a long way to go. In the near future we will be able to see if these documents were successfully used and applied for transparent and evidence-based decision making.